DESIGN AND CONSTRUCTION OF NOISE DETECTION DEVICE WITH ARDUINO-BASED SOUND SENSOR MIC IN THE LIBRARY - Wahjudi, Dody; Darmawan, Isra' Nuur; Kholistianingsih; Rifadila Fahmi, Ananda (Program Studi Teknik Elektro Universitas Peradaban, 2024)
The library holds the meaning as a place where various information is disseminated, whether printed or recorded in various media such as books, magazines, computers, and others. The library is a public place that provides information that can be visited by anyone, both children and adults are allowed to visit the library. Not apart from library visitors consisting of children to adults, it is not uncommon for disorder to occur inside the library, one of which is noise that can disturb the tranquility inside the library. Unexpected or unwanted noise because it does not match the library context can cause discomfort and disturbance to library visitors. Therefore, based on the considerations above, researchers try to propose research entitled